2012
DOI: 10.1002/bem.21725
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long‐term exposure to extremely low‐frequency magnetic fields on bone formation in ovariectomized rats

Abstract: The effects of long-term extremely low-frequency magnetic field (ELF-MF) exposure on bone formation and biochemical markers were investigated in ovariectomized rats. Sixty mature female Sprague-Dawley rats were randomly divided into four different groups (n = 15): (i) unexposed control (CTL); (ii) ovariectomized only (OVX); (iii) non-ovariectomized, exposed (SHAM + ELF-MF); and (iv) ovariectomized, exposed (OVX + ELF-MF). The third and fourth groups were exposed to 1.5 mT ELF-MF for 4 h a day for 6 months. Bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…[ 9 ] Indeed, EMF had been used for the past 25 years to approach different types of osteoporosis in both animal and clinical experiments. [ 10,11 ] Although it is known that orthodontic tooth movement is accompanied by site-specific bone remodelling,[ 12 ] limited number of studies [ 5,6 ] evaluated the effects of EMF on tooth movement. Therefore, the purpose of this study was to evaluate whether a 50 Hz extremely low frequency electromagnetic field (ELF-EMF) affects the extent of orthodontic tooth movement in rats.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Indeed, EMF had been used for the past 25 years to approach different types of osteoporosis in both animal and clinical experiments. [ 10,11 ] Although it is known that orthodontic tooth movement is accompanied by site-specific bone remodelling,[ 12 ] limited number of studies [ 5,6 ] evaluated the effects of EMF on tooth movement. Therefore, the purpose of this study was to evaluate whether a 50 Hz extremely low frequency electromagnetic field (ELF-EMF) affects the extent of orthodontic tooth movement in rats.…”
Section: Introductionmentioning
confidence: 99%
“…ELF-MFs include stimulation in the range of 0-300 Hz frequency and have biological effects on tissues. There are data showing that ELF-MFs cause functional changes in muscle, neural tissues and bones [12,13]; some researchers even claim that ELF-MFs may impair the ability of the SARS-CoV-2 virus to replicate and attack host cells [14]. It is indicated that ELF-MFs have a beneficial impact on brain tissue and its functions [15][16][17], suggesting that this stimulation method could be advantageous for patients after a stroke.…”
Section: Introductionmentioning
confidence: 99%